Physico-chemical and mechanical characterisation of the bark of selected Ficus species growing in Uganda - Mwanja, Christine; Mugabi, Paul; Banana, Abwoli Y. (European Journal of Wood and Wood Products, 2016)
In this study, the physical, chemical and mechanical properties of three Ficus species growing in Uganda were determined. Basic density and water absorption rate were (0.33 g/cm3, 134) in Ficus natalensis, (0.32 g/cm3, 137) in Ficus thonningii and (0.28 g/cm3, 145) in Ficus glumosa, respectively. Lignin content and tensile strength were highest in the bark of F. natalensis, and lowest in F. glumosa while cellulose content was highest in the bark of F. glumosa and lowest in F. natalensis. Based on the results, the bark is not suitable for use in industries such as paper manufacturing, where lignin is undesirable, but it can be used in manufacture of dyes and adhesives.
Keywords: Physico-chemical; Ficus species; Uganda